Pemanfaatan Kembali Pelayanan Kesehatan Oleh Pasien Umum Rawat Inap di Rumah Sakit Syekh Yusuf Tahun 2019 - Jumriati Jumriati; Muhammad Fais Satrianegara; Habibi Habibi (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
In this globalised era, hospitals do not only conduct social missions because the business aspect is an inevitable consequence. Therefore, it is common for hospitals to pull forward their profile promotion because of the services that they offer to connect users and providers. This research uses a quantitative approach with a cross-sectional research design. It observes dependant as well as independent factors through approaches, observations and data collection simultaneously. The research samples consist of 86 respondents. Each respondent is invited to an interview and observation only once in which the dependant and independent variables are examined at the time of data collection. The research findings indicate that hospital fee rates (p=0.000), the service quality (p=0.003), location (p=0.000), facilities (p=0.000) correlate with patients’ decision on the re-utilisation of hospitalisation health services while distance (p=0.0061) does not. Thus, this research concludes that while distance does not influence patients’ decision to re-utilise the hospitalisation health services, the service quality, location, and facilities make them consider re-utilising the services in Syekh Gowa Public Regional Hospital. This research recommends that the hospital keeps improving the quality of hospitalisation health services to win the competition with other hospitals. Keywords: predisposing factors, reinforcing factors, re-utilisation